Pembebasan Dan Mekanisme Pemberian Ganti Rugi Tanah Untuk Kepentingan Umum Dalam Hal Pembangunan Tempat Pemakaman Umum (TPU) di Kecamatan Sipatana - Siti Hardianti Paramata; Nur Mohamad Kasim; Dolot Alhasni Bakung (Lembaga Pengembangan Kinerja Dosen, 2024)
The aim of this research is to discuss the implementation of land acquisition for the public interest in terms of the construction of a public cemetery in Sipatana District and the mechanism for providing compensation. This research uses empirical legal methods, by presenting data based on field facts which are then analyzed descriptively qualitatively. The research results show that there are problems in acquiring land as the location for the TPU in question. This is marked by the sale and purchase of land to the government by other parties, who are still the family of the land owner, Mr Yamin Tolinggi. What this means is that the seller of the land is not the actual owner but just a nephew who happens to live at that location. Apart from that, the actual owner demands payment from the land, which is then confirmed by evidence and ownership rights based on court decisions. Disposal of land is a last resort and must obtain approval from the party entitled to the land, however, the land release was in error, where the government incorrectly provided compensation or payment to parties who were not actually the owners of the land. The mechanism for providing compensation for land acquisition by the government for the construction of TPU in Sipatana District is carried out by the Gorontalo Province and Gorontalo City governments on land covering an area of ​​27,766 m2 or around 2.7 hectares. However, land acquisition payments made by both the provincial and Gorontalo city governments were given to those who were not actually entitled to them. The total compensation for land acquisition was IDR 3.5 billion, but the entire amount was given to other parties. Therefore, the real owner then sued over his approximately 7,186 meter land and won in court, and in the end the Gorontalo provincial government awarded compensation of Rp. 750 million (seven hundred and fifty million rupiah) to land owners, through the 2023 APBD budget.